Pengaruh Kinerja Kepala Desa terhadap Peningkatan Pembangunan di Desa Batang Hari Ogan Kecamatan Tegineneng Kabupaten Pesawaran - Heri Yuda Novriawan; Yulianto Yulianto; Ani Agus Puspawati (Jurusan Ilmu Administrasi Publik FISIP Universitas Lampung, 2023)
This research aims to determine the influence of the performance village head on the improvement of development in the community of Batang Hari Ogan. The variables of performance are : Productivity, service quality, responsiveness, responsibility and accountability. The variables of development are : basic service, infrastructure conditions, accesbility, public services, government administration. The method used a descriptive verification with a survey approach. The population were communities are villagers of Batang Hari Ogan. The sample were 97 respondent with non probability sampling technique of purposive sampling type. The data collected through questionnaire. The hypotheses were tested by t test dan f test . The results revealed there was influence of performance village head on the improvement of development of Batang Hari Ogan. with the calculation of the t test by 5.389 > t table by 1,661. Then f test by 29,039 > f table by 3,100. This indicates that there is a influence between the performance village chief and development improvement variables. So the value of determination is 0,291 or 29,1% of village development is influenced by the performance of the village head. While the remaining 70.9% was influenced by other factors.